Bulletin 35 The Utilization of Fuel in Locomotive Practice - W. F. M. GOSS (The National Institute for Occupational Safety and Health (NIOSH), 1911)
The locomotives in service on the railroads of this country consume more than one-fifth of the total coal production of the United States. The amount is so large that any small saving that can be made effective in locomotive practice at once becomes an important factor in conserving the fuel supply of the nation. For this reason the United States Geological Survey gave attEmtion to the special problems of combustion in locomotive boilers. It approached this task from several different directions. The facts presented herewith constitute one series of results. In the fall of 1906 the locomotive-testing laboratory of Purdue University, at Lafayette, Ind., entered on a series of tests, one purpose of which was to determine in precise terms the degree of efficiency with which a modern high-class American locomotive utilizes the heat energy of the fuel supplied to it. The general interest in the subject, the elaborate plans which had been formulated for conducting the work, and the substantial character of the support which had been pledged to maintain it justified the Geological Survey in aiding the investigation. a The cooperation of the Survey consisted in detailing experts to assist the regular staff of the laboratory in the chemical and calorific work of the tests. These experts, working under the general supervision of the director of the Purdue laboratory, became responsible for the sampling of smoke-box gases, of the fuel used, of the cinders caught in the front end, of the sparks discharged by the stack, and of the refuse caught in the ash pan. The gas analyses were made by them at the university laboratory. The analyses of all solid samples and the calorific tests of the fuels were made at the government fuel-testing plant at St. Louis. The representatives of the Survey were not concerned with other phases of the work.